Smart card applications : - Rankl, Wolfgang (John Wiley & Sons Ltd., 2007)
Smart card technology has reached the stage of development where user needs and applications are the focus of attention in the field, rather than theoretical aspects. Because of this, Rankl (Giesecke & Devrient GmbH, Germany) has chosen to concentrate this handbook on proven solutions that can be implemented directly using available smart card operating systems. He describes reusable model solutions and modules that can be used to handle commonly occurring tasks and can be presented independently of actual program code. He covers architecture, implementation, and operation patterns; discusses practical issues of prerequisites and in-field faults; and presents illustrative use cases.